1994
DOI: 10.1021/j100078a027
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Holes in Alkanethiol Monolayers on Gold

Abstract: Self-assembled monolayers of alkanethiols (CnH2,,+lSH; n = 3, 8, 12, 18, and 22) adsorbed on gold(ll1) are investigated with (atomically resolved) scanning tunneling microscopy (STM) and wetting measurements. The characteristic depressions observed in these monolayers with STM are proven to be holes in the underlying top gold surface layer rather than defects in the thiol monolayer itself. The holes originate from an etching process of the gold during adsorption of the thiol molecules: a correlation is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(207 citation statements)
references
References 5 publications
(7 reference statements)
16
189
1
Order By: Relevance
“…As these observations were made under nitrogen atmosphere, and therefore no oxidation due to oxygen was possible, they could indicate etching of the copper nanoparticles in thiol-containing solutions. Similarly, etching of gold particles by thiols has been reported [39] and [40]. Additionally, similar trends were observed for the chain length and concentration of the thiol.…”
Section: Ligand Exchange and Etchingsupporting
confidence: 75%
“…As these observations were made under nitrogen atmosphere, and therefore no oxidation due to oxygen was possible, they could indicate etching of the copper nanoparticles in thiol-containing solutions. Similarly, etching of gold particles by thiols has been reported [39] and [40]. Additionally, similar trends were observed for the chain length and concentration of the thiol.…”
Section: Ligand Exchange and Etchingsupporting
confidence: 75%
“…8). As discussed above, the reduced gold surface can weaken the Au-Au bond; (2) the formation of SAMs on gold surfaces may weaken the interactions between gold atoms in the top and lower layers because earlier scanning tunnelling microscopy studies have shown the mobility of Au thiolates within the SAMs of alkanethiols 62,63 .…”
Section: Resultsmentioning
confidence: 99%
“…19,50 Scanning tunneling microscopy (STM) studies (see section 3) suggest that the gold is slightly etched during self-assembly; gold has been detected in the deposition solution. 88,89 To remove kinetically trapped disordered states, the SAM is sometimes annealed by soaking it in hot deposition solution, 90 exposing it to warm temperatures in a gaseous ambient, 91 or subjecting the electrode to a cyclic voltammogram (CV) and repeated immersions in the deposition solution. 92 When two thiols are being co-deposited, the solvent, time and temperature all affect the mole fraction of each component in the SAM.…”
Section: Solution Adsorptionmentioning
confidence: 99%